Postural and manual therapy in temporomandibular dysfunctions - Esmhirna Liberalino Vilar; Joicinara Luz Sousa Pachêco Bezerra; Caian Guimarães Lima Façanha; Renata Bessa Pontes (Associação Brasileira de Odontologia, 2018)
Objective: to show the benefits of manual and postural therapy in temporomandibular joint alterations and to cite the techniques that can be used to treat these dysfunctions. Material and Methods: a narrative review of the scientific literature on the subject was carried out in books of the Physiotherapy and Dentistry areas, scientific articles through periodicals and sites, referring to publications of the last eighteen years, using as keywords: manual and postural therapy, temporomandibular joint dysfunctions, and temporomandibular joint. Results: 1.930 studies were found, of which 602 were selected for title/abstract reading, being 564 of them excluded due to lack of compliance with the inclusion criteria; thus, a total of 38 references were included. The literature reports several manual and postural techniques as beneficial resources for the treatment of temporomandibular joint alterations since they act from prevention to rehabilitation phases, regrouping the compromised muscles and recovering the functionality of the ear-jaw articulation. Conclusion: Physical Therapy, together with manual and postural therapy techniques, is important for the treatment of temporomandibular joint changes since its objectives are to activate blood circulation, relieve pain, promote muscle relaxation, and re-educate posture, aiming to promote patient well-being.